Population dynamics and biodiversity during spontaneous fermentation of Garcinia mangostana pericarps / Mohamad Sufian So’aib and Nik Abdul Hafiidz Nik Abdul Malek - Nik Abdul Malek, Nik Abdul Hafiidz; So’aib, Mohamad Sufian (Universiti Teknologi MARA Shah Alam, 2018)
This study investigates the population dynamics and microbial diversity during spontaneous fermentation of Garcinia mangostana pericarp (GMP). The spontaneous fermentation was carried out anaerobically for 100 days. Population dynamics was determined by enumerating pure isolates on different selective media. The microorganism’s identities were determined from the amplified 16S rDNA and 5.8S-ITS rDNA genes of bacteria and yeasts respectively. LAB and yeast were prevalent during fermentation at 103−104 cfu/ml and 103−107 cfu/ml, respectively. Around eight bacterial genera such as Klebsiella, Enterobactor, Mangrovibactor, Escherichia, Cronobactor, Komagataeibacter, Lactobacillus and Bacillus whereas five yeast genera Meyerozyma, Saccharomycete, Hanseniaaspora, Mycobacterium and Pichia were detected. Lactobacillus brevis and Lactobacillus plantarum were amongst LAB species identified. Lactic acid was suspected to promote LAB growth and total inhibition of pathogens after 21 days. The results highlighted potential starter culture consortium for future product development and conferred the microbiological safety of spontaneously fermented GMP product.